Development of generic student engagement scale in higher education: An application on healthcare students - Shuang Li; Stephen Wai Hang Kwok; Summer Cho Ngan Siu; Jessie Yuk Seng Chung; Hemio Chung Yan Lam; Eva Yuen Mei Tsang; Kam Cheong Li; Joanna Wing Yan Yeung; Simon Ching Lam (Wiley, 2023)
Abstract Aim Student engagement is an important factor to the success of higher education. This study aimed to develop a Generic Student Engagement Scale (GSES) for face‐to‐face and online learning. Design This was a cross‐sectional psychometric study. Methods We tested the psychometric properties of GSES in 451 students at the school of nursing and health studies undertaking online and face‐to‐face learning at a local university in Hong Kong between 2016 and 2018. Results Content validity, face validity and test-retest reliability of GSES were satisfactory. The 29‐item GSES contains five factors "self‐regulated learning," "cognitive strategy use," "experienced emotion," "teacher-student interaction," and "enjoyment of school life" with the good model fit. The GSES is a reliable and valid psychometric instrument to measure student engagement in face‐to‐face and online learning among undergraduates and higher diploma students. Our results implied that student engagement can be assessed in routine or research by using our instrument.